'Because I've been extremely careful': HIV seroconversion, responsibility, citizenship and the neo-liberal drug-using subject. (17th February 2017) - Krüsi, Andrea; McNeil, Ryan; Moore, David; Small, Will
Abstract : In this article, we examine how injection drug users who do not attribute their HIV infection to engaging in HIV risk behaviours take up and critique discourses of individual responsibility and citizenship relating to HIV risk and HIV prevention. We draw on data from a study in Vancouver, Canada (2006–2009) in which we interviewed individuals living with HIV who had a history of injection drug use. In this paper, we focus on six cases studies of participants who did not attribute their HIV infection to engaging in HIV risk behaviours. We found that in striving to present themselves as responsible HIV citizens who did not engage in HIV risk behaviours, these participants drew on individually focused HIV prevention discourses. By identifying themselves in these ways, they were able to present themselves as 'deserving' HIV citizens and avoid the blame associated with being HIV positive. However, in rejecting the view that they and their risk behaviours were to blame for their HIV infection and by developing an explanation that drew on broader social, structural and historical factors, these individuals were developing a tentative critique of focus on individual responsibility in HIV transmission as opposed to dangers of infection arising from the socio-economic environment. By framing the risk of infection in environmental rather than individual risk-behaviour terms, these individuals redistributed responsibility to reflect the social-structural realities of their lives. In this article, we reflect on the implications of these findings for public health measures such as risk prevention messages. We argue that it is important that such messages are not restricted to individual risk prevention but also include a focus of broader shared responsibilities of HIV.